Classic selective sweeps were rare in recent human evolution - Hernandez, Ryan D. (2011)
Efforts to identify the genetic basis of human adaptations from polymorphism data have sought footprints of “classic selective sweeps”. Yet it remains unknown whether this form of natural selection was common in our evolution. We examined the evidence for classic sweeps in resequencing data from 179 human genomes. As expected under a recurrent sweep model, diversity levels decrease near exons and conserved non-coding regions. In contrast to expectation, however, the trough in diversity around human-specific amino acid substitutions is no more pronounced than around synonymous substitutions. Moreover, relative to the genome background, amino acid and putative regulatory sites are not significantly enriched for alleles that are highly differentiated between populations. These findings indicate that classic sweeps were not a dominant mode of adaptation over the past ~250,000 years.